Rekonstruksi Evaluasi Sistem Penjaminan Mutu Eksternal PTKI Berbasis Total Quality Management dan Maqāṣid al-Syarī‘ah - Merita Diana; Subandi; Deden Makbuloh; Ahmad Fauzan (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
External quality assurance in Islamic higher education requires an evaluation model that moves beyond administrative compliance toward continuous improvement, ethical governance, and value-based institutional transformation. This study aims to reconstruct the evaluation of the External Quality Assurance System for Islamic Higher Education Institutions through the integration of Total Quality Management and maqāṣid al-syarī‘ah. The study employed qualitative document analysis and literature review. The corpus consisted of 31 key sources comprising national quality assurance regulations, accreditation instruments, Islamic higher education quality assurance guidelines, foundational theories, and scholarly literature on quality assurance, quality culture, Total Quality Management, accreditation, digital quality assurance, and maqāṣid al-syarī‘ah published or used within the 1986–2026 range. Data were analysed using thematic synthesis, theoretical comparison, and source triangulation. The findings reveal four major themes: the shift toward outcome-based and evidence-based accreditation, the persistence of compliance-oriented practices, the gap between formal quality systems and institutional quality culture, and the relevance of maqāṣid al-syarī‘ah as an ethical framework for reconstructing accreditation. The integration of Total Quality Management strengthens the logic of continuous improvement, while maqāṣid al-syarī‘ah reframes accreditation as a mechanism to protect religion, intellect, life, property, and future generations. This study contributes a value-based continuous improvement framework for reconstructing external quality assurance in Islamic higher education.